Growth and Productivity of Brown Midrib Sorghum Mutant Line Patir 3.7 (Sorghum bicolor L. Moench) Treated with Different Levels of Nitrogen Fertilizer - R. Sriagtula; S. Sowmen; Q. Aini (Tropical Animal Science Journal, 2019)
The study aimed to determine the best of nitrogen fertilizer level based on growth and biomass production of brown midrib sorghum mutant line Patir 3.7. This research was conducted at the Field Laboratory in the Faculty of Animal Science, Andalas University, Padang. The experiment was assigned in a completely randomized block design with 4 levels of nitrogen fertilizer application and 3 replications. The treatments consisted of N0= 0 kg N ha-1 as a control; N1= 50 kg N ha-1; N2= 100 kg N ha-1; and N3= 150 kg N ha-1. Agronomic and production variables measured were plant height, stem diameter, leaf width length, leaf stem panicle ratio, stem Brix sugar content, as well as fresh biomass and nutrient production. Analysis of variance followed by Duncan Multiple Range Test (DMRT) was conducted. The results showed that the addition of nitrogen fertilizer produced the highest stem diameter, leaf length, leaf width, leaf ratio, and stem ratio (p<0.05). However, the panicle ratio and stem Brix sugar contents were not significantly affected (p>0.05) by the level of nitrogen fertilizer. The fresh biomass, dry matter, crude protein, ash, NFE, and TDN production increased significantly (p<0.05) with the increased level of nitrogen fertilizer. Based on those findings, it can be concluded that nitrogen fertilizer application at the level of 50 kg N ha-1 produces better growth, fresh biomass, dry matter, and nutrients production.